2002
DOI: 10.1177/152660280200900423
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Angioscopy Using 3-Dimensional Rotational Digital Subtraction Angiography for Endovascular Assessment

Abstract: 3D DSA and virtual angioscopy are novel techniques that have been successful in recreating images of blood vessels immediately after angiography. These techniques could be useful as additional imaging modalities to complement computed tomography or magnetic resonance imaging in the evaluation of vascular diseases after endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Other invasive approaches, ie, elastography, 2 angioscopy, 3 thermography, 4 and intravascular ultrasound, 5,6 are designed to characterize late-stage vascular disease. In contrast, magnetic resonance imaging (MRI) offers a unique, noninvasive opportunity for sensitive detection and characterization of atherosclerotic disease.…”
mentioning
confidence: 99%
“…Other invasive approaches, ie, elastography, 2 angioscopy, 3 thermography, 4 and intravascular ultrasound, 5,6 are designed to characterize late-stage vascular disease. In contrast, magnetic resonance imaging (MRI) offers a unique, noninvasive opportunity for sensitive detection and characterization of atherosclerotic disease.…”
mentioning
confidence: 99%
“…Virtual cisternoscopy was the fi rst described in the clinically relevant use of virtual endoscopy to achieve fl ythrough non-invasive imaging of the intracranial anatomic structures and vasculature topography [7] . Virtual endoscopic angioscopy is a new technique for the visualization of the internal surface of the vasculatures and aneurysms that allows fl ythrough views of the occlusive vascular pathology including the aneurysm orifi ce, intra-aneurysmal thrombi, and aneurysm wall calcifi cations [2,4,17] . Although such techniques are being increasingly used for preoperative evaluations they are rarely employed in perioperative procedures.…”
Section: Discussionmentioning
confidence: 99%
“…47 Although virtual angioscopic images acquired from angiographic data may help detect and classify endoleaks, this technique is still invasive compared to CT-VIE or MR-VIE. 48 Armerding et al 47 found no advantage of postprocedural DSA over CTA in the detection of postdeployment complications.…”
Section: Digital Subtraction Angiography (Dsa)mentioning
confidence: 99%